Dental malocclusion and its relationship to harmful oral habits - Miriam Veronica Lima Illescas; Agustín Rodríguez Soto; Brismayda García González (Editorial Ciencias Médicas, 2019)
Introduction: Malocclusion is triggered by rupture of the balance between extraoral and intraoral forces as a result of an anomalous function. Such anomalous muscular functions are known as harmful oral habits. Objective: Update knowledge and analyze factors related to dental malocclusions, such as harmful oral habits in children, in terms of the frequency and duration of nutritive and non-nutritive sucking, mouth breathing and atypical tongue thrust. Methods: A bibliographic review was conducted of papers published in the last five years in the digital databases Pubmed, Lilacs, Ibecs and Cumed. The search terms used were malocclusion, habits, finger sucking, pacifiers, bottle feeding, tongue habit and mouth breathing in English, and maloclusión, hábitos, succión del dedo, chupete, biberones, hábitos linguales and respiración por la boca in Spanish. 65 papers were obtained, of which only 39 met the inclusion criteria. Data analysis and integration: 89.5 % of the papers corresponded to studies about non-nutritive sucking habits alone or in combination with other habits, whereas 10.5 % dealt with studies about mouth breathing children. Only 26.31 % of the studies selected took into account the variables duration and frequency of the habits. Nutritive sucking habits were found to be associated with overjet, posterior crossbite and distal step. A relationship was also found between a short breastfeeding period and the prevalence of non-nutritive sucking habits, with the presence of anterior open bite alongside the aforementioned malocclusions. Mouth breathing was related to class II, small retrognathic jaw and a decreased lower third of the face. Conclusions: Numerous studies have been conducted to determine the relationship between malocclusions and the duration of nutritive and non-nutritive sucking habits, without considering the frequency of such habits. On the other hand, the electronic databases consulted contain few studies about mouth breathing and atypical tongue thrust in children.